Loss to follow-up and mortality among HIV-infected people co-infected with TB at ART initiation in Durban, South Africa - Bassett, Ingrid V. (2012)
OBJECTIVE: To quantify the impact of TB co-infection on death and loss to follow-up (LTFU) 12 months after entry into an ART program. DESIGN: Prospective intervention study METHODS: From May 2007-2008, patients undergoing pre-ART training in Durban, South Africa were screened for pulmonary TB using mycobacterial culture. Subjects missing appointments for >3 months were phoned. Patients who could not be reached were considered LTFU. Deaths were ascertained by report from family members. We used the Kaplan-Meier method to estimate time to LTFU or death for 3 groups at enrollment: 1) newly-diagnosed with TB by sputum culture; 2) on TB treatment (i.e. previously-diagnosed); and 3) TB free. We evaluated the role of TB on mortality and LTFU using Cox proportional hazards models. RESULTS: Nine-hundred fifty-one HIV-infected subjects were enrolled; 59% were female and median baseline CD4 count was 90/μl (IQR 41-148/μl). One hundred forty-four (15%) were newly-diagnosed with TB by sputum culture; an additional 199 (21%) were already on TB treatment. By 12 months, 26% newly-diagnosed with TB at enrollment died or were LTFU, compared to 19% already on TB treatment, and 14% who were TB free (p=0.001). Controlling for age, sex, smoking, CD4, and opportunistic infection history, subjects newly-diagnosed with pulmonary TB were 76% more likely to die or be LTFU (HR 1.76, 95% CI 1.20-2.60) than those without TB. CONCLUSIONS: HIV/TB co-infected individuals are more likely to die or be LTFU within 12 months of ART clinic entry in South Africa. These patients require intensive follow-up during ART initiation.